INCREASING CRITICAL THINKING SKILLS THROUGH STEM-PJBL LEARNING MODELS: RESEARCH TREND AND SYSTEMATIC LITERATURE REVIEW - Azzahra, Miftahul Zannah; Anggereini, Evita; Yusnaidar, Yusnaidar (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
This study aims to analyze research trends on the effectiveness of STEM-PjBL learning models in improving students' critical thinking skills through a systematic literature review from 2013 to 2024. The research employs a bibliometric approach and follows the PRISMA framework to select and analyze 32 articles from the Scopus database. The results indicate that the implementation of STEM-PjBL significantly enhances students' critical thinking skills, particularly when integrated with technology and interactive learning tools. The analysis highlights trends in research focus, dominant contributing countries, and the most cited studies. Indonesia emerges as the leading contributor to STEM-PjBL research. Additionally, bibliometric visualizations using VOSviewer reveal key themes, including project-based learning models and their impact on 21st-century skills. The findings contribute to the advancement of science and technology education, offering valuable insights for educators and policymakers to develop more adaptive and effective curricula. Despite its contributions, this study is limited by potential publication bias and the absence of meta-analytical findings.